2021
DOI: 10.1016/j.clinthera.2020.12.018
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obesity and Associated Fatty Acids on Placental Inflammation

Abstract: Purpose: Maternal obesity, affecting nearly 1 in 4 pregnancies, is associated with increased circulating saturated fatty acids, such as palmitate. These fatty acids are implicated in placental inflammation, which may in turn exacerbate both maternalefetal tolerance and responses to pathogens, such as group B Streptococcus. In this review, we address the question, "How do obesity and associated fatty acids influence placental inflammation?" Methods: In this narrative review, we searched PubMed and Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 134 publications
0
13
0
Order By: Relevance
“…The Prediction and Prevention of Preeclampsia and Intrauterine Growth Restriction study indicated that persistently high levels of maternal inflammation during pregnancy increased the risk of neurodevelopmental delay in children in cognitive, motor and social areas, and children of mothers with the highest levels of inflammation had the largest number of neurodevelopmental delay areas [ 35 ]. Maternal prepregnancy obesity or excessive weight gain during pregnancy would lead to chronic systemic inflammation and placental inflammatory response, causing increased concentrations of pro-inflammatory cytokines such as IL-6, IL-8, tumor necrosis factor-α (TNF-α) and C-reactive protein (CRP) [ 36 , 37 ]. Exposure to an inflammatory environment in early life affects the development and function of fetal microglia, which are related to essential neurodevelopmental functions such as neuronal proliferation and differentiation, synapse formation, myelin formation and establishment of connections [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Prediction and Prevention of Preeclampsia and Intrauterine Growth Restriction study indicated that persistently high levels of maternal inflammation during pregnancy increased the risk of neurodevelopmental delay in children in cognitive, motor and social areas, and children of mothers with the highest levels of inflammation had the largest number of neurodevelopmental delay areas [ 35 ]. Maternal prepregnancy obesity or excessive weight gain during pregnancy would lead to chronic systemic inflammation and placental inflammatory response, causing increased concentrations of pro-inflammatory cytokines such as IL-6, IL-8, tumor necrosis factor-α (TNF-α) and C-reactive protein (CRP) [ 36 , 37 ]. Exposure to an inflammatory environment in early life affects the development and function of fetal microglia, which are related to essential neurodevelopmental functions such as neuronal proliferation and differentiation, synapse formation, myelin formation and establishment of connections [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although levels of both the saturated fatty acid palmitate and the monounsaturated fatty acid oleate are elevated in obese pregnant women [113], only exposure to palmitate facilitated the development of ER stress in the syncytiotrophoblast, driving translocation of ATF4 and downstream apoptosis mediated by C/EBP homologous protein (CHOP). Furthermore, increased placental palmitate content drives a potent inflammatory response in the obese placenta, including activation of the inflammasome and secretion of inflammatory cytokines [62,114]. This inflammatory response is likely to form a reciprocal cause-and-effect relationship with placental ER stress [91,104,115,116].…”
Section: Trends In Molecular Medicinementioning
confidence: 99%
“…Palmitic acid (PA, 16:0) and oleic acid (OA, 18:1) constitute 60% of fatty acids in lipids present in the maternal plasma by the end of pregnancy, and in both placenta and the fetus, these fatty acids act as fuel and as building blocks for the synthesis of structural and signaling lipids [ 6 , 7 , 8 ]. Both PA and OA are derived from diet and endogenous synthesis; thus, the fetus relies on both transplacental transfer and endogenous fetal–placental synthesis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excess PA is often negatively depicted for its potential involvement in the pathophysiology of adult chronic diseases such as cardiovascular disorders and diabetes, and excess intracellular un-esterified PA may induce lipotoxic effects [ 7 , 8 ], including in the placenta [ 10 ]. However, PA is also an essential fuel source, is a constituent of many signaling lipid molecules, is needed for the regulation of enzymatic activity though palmitoylation [ 7 ], and is involved in the production of pro-inflammatory cytokines [ 11 ], which are important in regulating pregnancy health and parturition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation